Current status and development opportunity analysis of small and medium sized businesses in Moscow region (Russia) - Sergey Ditev; Alexander Vaskin (European Regional Science Association (ERSA), 2002)
Economic changes in Russia have created a foundation for establishment and development of private property and launched the basic principles of market regulation. They have also led to tremendous changes in people`s psychology and surrounding world perception. Under the circumstances small and medium sized businesses have become of great importance for modern economy and will be one of the main factors for further economic growth in Russia. Moscow region is one of parts of Russia where we can find important changes made lately in this field: there have been created a state authority for support and development of small and medium sized businesses; dozens of specialized training centers, consulting and leasing companies have opened; a whole-new infrastructure needed for rapidly growing businesses arises - in respect to this process international assistance makes significant contribution. A period of small and medium sized business development associated with 'quick and easy' profits gained mainly in multiple resale operations is over now. A new stage comes into being where effective management of the business is the key factor of success. Therefore, this stage of evolution has much tougher requirements for economic, law and infrastructure background in the country as a whole and Moscow region as a part of it. The paper touches upon the main problems that small and medium sized businesses face today in Moscow region. Analysis of small and medium sized business in Moscow region and current state policy in this sphere has led the authors to several conclusions they would like to share in the paper.
Keywords: 330